Enhanced thermoelectric performance of Te-doped skutterudite with nano-micro-porous architecture. (15th January 2019) - Yang, Houjiang; Wen, Pengfei; Zhou, Xilong; Li, Yao; Duan, Bo; Zhai, Pengcheng; Zhang, Qingjie
Abstract: Te-doped Co4 Sb11.5 Te0.5 materials with nano to micro sized pores are fabricated tactfully by annealing the nano-Co4 Sb11.5 Te0.5 /Co4 Sb11.5 Te0.5 composites. The annealed samples present a dramatically reduced thermal conductivity due to the abundant scattering of phonons in a wide wavelength range by the obtained all-scale porous architecture. Meanwhile, the Seebeck coefficient is enhanced for the annealed samples due to the lower carrier concentration. The sample annealed 100 h exhibits an enhanced dimensionless figure of merit of 1.2 at 800 K, increased by 33.7% as compared with that of the dense sample. Graphical abstract: Unlabelled Image